Adopting STEAM Development Strategies in Early Years Education in Nairobi City County, Kenya: Implication For 21st Century Skills - Ganira, Lilian (Universitas Terbuka, 2022)
Integration of Science, Technology, Engineering, Art, and Maths (STEAM) ideals in Early Years Education (EYE) builds a strong foundation for learners to discover, explore, play, discuss and experiment with the environment. Given that the goal of EYE is to expand an understanding of the world through observation, experimentation, and exploration, the integration of STEAM activities requires an intentional connection between lesson design and implementation for long life learning. Skills of creativity, collaboration, critical thinking, communication, and inquiry processes embedded in STEAM concepts prepare learners to develop a scientific mindset for solving global challenges. Therefore, the study determined the influence of STEAM strategies on the development of creativity, collaboration, critical thinking, and communication skills among learners in Nairobi City County, Kenya. Based on a descriptive survey design, the study purposively sampled 107 teachers in EYE, 99 head teachers, and 55 parents. The teacher questionnaire, which anchored the study in data collection, was complemented by observation of class activities and documentary analysis. Multiple intelligence theory was adopted to explore the nexus between STEAM and core competencies required for survival in the 21st century. Results illustrated that even though teachers in EYE implemented STEAM activities, which resulted in the development of creativity, collaboration, critical thinking, and collaboration skills, there exist challenges emanating from pedagogy and inadequate support for instructional resources. The study recommends that teachers should be equipped with tools and resources for integrating STEAM activities in EYE, considering the nature of practices to apply and attributes that may promote or deter learning.